Temporal pattern of dengue cases in central zones of Shah Alam: A retrospective study from 2013 to 2016 / Nazri Che Dom, Fatin Azura Saiful Bahri , Muhammad Syukri Rahmat - Che Dom, Nazri; Saiful Bahri, Fatin Azura; Rahmat, Muhammad Syukri (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Understanding on the temporal pattern of dengue is important in attempt to plan the strategy for controlling its occurance. Therefore, this study was designed to identify the temporal pattern of dengue cases in central zone of Shah Alam, Selangor. Four time series data were being divided into two periods to examine the corresponding weekly cumulative percentages of case numbers for each period. Then three cut-off points were evaluated by observing the trend behavior of DF for each year and was further analyzed using Pearson's correlation coefficient. The result obtainedimplied that the temporal pattern of dengue cases in 2013 was markedly different when compared to the other three years (2014, 2015 and 2016). It was found that the temporal pattern of dengue cases has changed from 2013 to 2016 as the number of dengue cases in 2013 was high during the end of the year while for the rest;the number of cases was low during end of the year but slightly higher during the first 26 epid week. This study showed that the temporal pattern of dengue cases in the central zone of Shah Alam are differ for the last 4 years of occurrence. However the numbers are still increasing from year to year and proper preventive measures should be carried out to break the chain of the transmission.